2022
DOI: 10.1002/ptr.7374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanocurcumin supplementation on the severity of symptoms and length of hospital stay in patients with COVID‐19: A randomized double‐blind placebo‐controlled trial

Abstract: It has been more than a year since the outbreak of COVID-19, and it is still the most critical issue of the healthcare system. Discovering effective strategies to treat infected patients is necessary to decrease the mortality rate. This study aimed to determine the effects of nanocurcumin on the severity of symptoms and length of hospital stay (LOS) in COVID-19 patients. Forty-eight COVID-19 patients were randomly assigned into nanocurcumin (n = 24) and placebo (n = 24) groups receiving 160 mg/day nanocurcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
(38 reference statements)
1
32
0
1
Order By: Relevance
“…Regarding the inflammatory index of CRP, the results of prior studies were also contradictory. Some studies, such as Shafie et al, have reported consistent results with the present study and did not observe any significant effect of nano-curcumin supplementation on CRP levels [ 39 ], while clinical and systematic reviews, in this case, have reported positive effects of various forms of curcumin supplements on CRP levels [ 26 , 37 ]. It should be noted that the proposed mechanism of studies observing the positive effects of curcumin supplementation on clinical signs and inflammatory markers has been stated that curcumin can have beneficial effects on gene expression and balance between pro-inflammatory (IL-6 and IL-1β) and anti-inflammatory factors (IL-10, IL-35, and TGF-α) and in this way, it can exert its effects on the control of this disease [ 26 , 29 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the inflammatory index of CRP, the results of prior studies were also contradictory. Some studies, such as Shafie et al, have reported consistent results with the present study and did not observe any significant effect of nano-curcumin supplementation on CRP levels [ 39 ], while clinical and systematic reviews, in this case, have reported positive effects of various forms of curcumin supplements on CRP levels [ 26 , 37 ]. It should be noted that the proposed mechanism of studies observing the positive effects of curcumin supplementation on clinical signs and inflammatory markers has been stated that curcumin can have beneficial effects on gene expression and balance between pro-inflammatory (IL-6 and IL-1β) and anti-inflammatory factors (IL-10, IL-35, and TGF-α) and in this way, it can exert its effects on the control of this disease [ 26 , 29 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
“…For example, as mentioned in our study, only the feeling of weakness of the patients participating in the intervention group was significantly reduced compared to the control group, while in the other studies, most of the clinical symptoms such as weakness, muscle fatigue, cough, chill, sore throat, etc. have significantly decreased [ 8 , 24 , 37 39 ]. Regarding the inflammatory index of CRP, the results of prior studies were also contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Em um dos ensaios observou-se melhora na fraqueza dos pacientes (este achado foi avaliado por meio de entrevista com os participantes), mas nenhuma alteração clínica ou bioquímica foi observada (Askari et al, 2022). No outro, houve melhora na saturação do O2, mas nenhuma outra diferença significativa nos parâmetros medidos foi observada (Honarkar-Shafie et al, 2022). Estudos que utilizaram a curcumina como adjuvante, no entanto não divulgaram dados referentes a outras intervenções administradas aos pacientes.…”
Section: Alimentos E Especiariasunclassified
“…Curcumin is re-proposed as a potential antiviral key for the treatment of SARS-CoV-2 based on its relation to the infection pathways. Moreover, the use of curcumin-loaded nanocarriers for increasing its bioavailability and therapeutic efficiency was highlighted in several clinical trials ( Dourado et al, 2021 ; Hassaniazad et al, 2021 ; Tahmasebi et al, 2021a ; Tahmasebi et al, 2021b ; Valizadeh et al, 2020 ; Hassaniazad et al, 2020 ; Ahmadi et al, 2021 ; Saber-Moghaddam et al, 2021 ; Asadirad et al, 2022 ; Honarkar Shafie, et al, 2022 ). Additionally, the potential of the nanostructured systems and their synergistic action with curcumin on the molecular targets for viral infections have been explored ( Hassaniazad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One report illustrates that the administration of nano-curcumin can accelerate recovery from the acute inflammatory phase of COVID-19 by mediating inflammatory immune responses (decrease in serum IFN-γ and IL-17, TBX21 mRNA; increase in serum IL-4 and TGF-β, FOXP3 mRNA) ( Ahmadi et al, 2021 ). COVID-19 patients receiving nano-curcumin supplements could significantly increase the O 2 saturation and decrease the scores of the Wisconsin Upper Respiratory System Survey (WURSS-24) in the third domain, fourth domain, and total score, indicating nano-curcumin supplementation could help decrease hypoxia and moderate the symptoms induced by SARS-CoV-2 infection ( Honarkar Shafie, et al, 2022 ). After nano-curcumin treatment, a significant reduction in the frequency of Th17 cells, downregulation of Th17 cell-related factors, and decreased levels of Th17 cell-related cytokines were found in mild and severe COVID-19 patients, implying that curcumin could be a potential modulatory compound in improving the patient’s inflammatory condition ( Hassaniazad et al, 2020 ; Saber-Moghaddam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%